The Importance of Reversible Scavenging for the Marine Zn Cycle Evidenced by the Distribution of Zinc and Its Isotopes in the Pacific Ocean. Issue 4 (20th April 2023) - Sieber, M.; Lanning, N. T.; Bian, X.; Yang, S.‐C.; Takano, S.; Sohrin, Y.; Weber, T. S.; Fitzsimmons, J. N.; John, S. G.; Conway, T. M.
Abstract: The North Pacific has played an important role in ongoing discussions on the origin of the global correlation between oceanic dissolved Zn and Si, while data in the North Pacific have remained sparse. Here, we present dissolved Zn and δ 66 Zn data from the US GEOTRACES GP15 meridional transect along 152°W from Alaska to the South Pacific. In the south (<20°N) Zn and Si exhibit a tight linear correlation reflecting strong Southern Ocean influence, while in the north (>20°N) an excess of Zn relative to Si in upper and intermediate waters is due to regeneration of Zn together with PO4 . Using a mechanistic model, we show that reversible scavenging is required as an additional process transferring Zn from the upper to the deep ocean, explaining the deep Zn maximum below the PO4 maximum. This mechanism applied for reversible scavenging also provides an explanation for the observed isotope distribution: (a) fractionation during ligand binding and subsequent removal of residual heavy Zn in the upper ocean, drives the upper ocean toward lower δ 66 Zn, while (b) release of heavy Zn then coincides with the PO4 maximum where carrier particles regenerate, causing a mid‐depth δ 66 Zn maximum. In the upper ocean, seasonal physical stratification is an additional important process influencing shallow δ 66 Zn signals. At the global scale, this mechanism invoking fractionation during ligand binding coupled with reversible scavenging offers a global explanation for isotopically light Zn at shallow depths and corresponding elevated mid‐depth δ 66 Zn signals, seen dominantly in ocean regions away from strong Southern Ocean control. Plain Language Summary: Zinc (Zn) is a vital micronutrient for marine phytoplankton and shows a global distribution similar to dissolved silicon, with greatest enrichment deeper than the macronutrients phosphate and nitrate. The correlation between Zn and silicon arises from their similar biogeochemical behavior in the Southern Ocean and the large‐scale circulation. In this study, we investigate the distribution of Zn and its isotopes along a transect from Alaska to the South Pacific. Using a mechanistic model, we show that adsorption of Zn onto sinking organic particles, termed reversible scavenging, transfers Zn from the upper ocean to depths, providing an explanation for the observed deep Zn maximum below the phosphate maximum. Furthermore, the applied mechanism for reversible scavenging is consistent with the observed Zn isotope distribution. In the upper ocean, removal of isotopically heavy Zn via scavenging leads to enrichment of light Zn in surface waters. The heavy Zn is released back to the water column where carrier particles remineralize, causing an enrichment of heavy Zn at mid‐depth (∼1, 000 m). At the global scale, our mechanism offers an explanation for isotopically light Zn at shallow depths and corresponding elevated mid‐depth signals, seen dominantly in ocean regions away from strong Southern Ocean control. Key Points: Regeneration of Zn together with PO4 and reversible scavenging play important roles for the Zn‐Si relationship in the North Pacific Fractionation during ligand binding coupled with reversible scavenging of Zn can explain the large‐scale δ 66 Zn distribution Seasonal physical stratification is an important process influencing surface and subsurface δ 66 Zn signals in the North Pacific